Chronic heart failure: prevention and treatment options - S. B. Migutina (Медицинский совет, 2013)
The problem of chronic heart failure remains relevant today. According to the Age of CHF study, the prevalence of this disease in this country is 12%. In 66% of cases CHF has ischemic etiology. Rational approach to treatment and evaluation of all possible risks significantly improves patient's condition and reduces severity of the disease. Non-drug treatments include low-salt diet and physical rehabilitation based on balanced aerobic activity.Despite a huge list of drugs recommended and used at CHF, attention to medicines called myocardial cytoprotectors remains high.